2017
DOI: 10.7567/jjap.56.09na02
|View full text |Cite
|
Sign up to set email alerts
|

Optical memory system based on incoherent recorder and coherent reader of multiplexed computer generated one-dimensional Fourier transform holograms

Abstract: The present article highlights the development results of archive memory holographic system based on application of computer generated Fourier holograms. The proposed idea allows realization of holographic principles of digital data record using simple and compact optical devices. Special interest is paid to synthesis and multiplexed record of one-dimensional Fourier transform holograms. The principal schemes of constructed prototypes of incoherent data recorder and coherent data reader are described in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…The new methods were copyrighted by three patents of the Russian Federation [37,38]. The experimental prototype of the system was built and contained an incoherent projection recorder and an anamorphic optics-based coherent reader [39,40]. The research results were presented at numerous conferences in Russia such as HOLOEXPO and Photonics and Information Optics, and international meetings such as Digital Holography and 3D Imaging 2015 in Shanghai, International Symposium on Optical Memory 2016 in Kyoto, where it was invited as plenary speech, Holography: Advances and Modern Trends 2017 in Prague and many others.…”
Section: The Birth and Development Of Holographic Data Storage Archit...mentioning
confidence: 99%
“…The new methods were copyrighted by three patents of the Russian Federation [37,38]. The experimental prototype of the system was built and contained an incoherent projection recorder and an anamorphic optics-based coherent reader [39,40]. The research results were presented at numerous conferences in Russia such as HOLOEXPO and Photonics and Information Optics, and international meetings such as Digital Holography and 3D Imaging 2015 in Shanghai, International Symposium on Optical Memory 2016 in Kyoto, where it was invited as plenary speech, Holography: Advances and Modern Trends 2017 in Prague and many others.…”
Section: The Birth and Development Of Holographic Data Storage Archit...mentioning
confidence: 99%
“…Первый основан на использовании некогерентного излучения и оптической проекционной системы для регистрации МПИ изображения МГФ с заданным линейным увеличением с последующим цифровым восстановлением кодированного изображения при использовании алгоритма обратного БПФ. Второй способ [9] основан на освещении МГФ когерентным лазерным излучением с использованием объектива, осуществляющего преобразование Фурье над МГФ, и матричного приемника, регистрирующего восстановленное кодированное изображение. При подсветке когерентным излучением пропускающей микроголограммы, наносимой на отражающую или рассеивающую подложку, в восстановленном фурье-объективом изображении коди-рованного изображения будет присутствовать значительный уровень спекл-шума от голограммы и подложки.…”
Section: проведение эксперимента по считыванию и декодированию мгфunclassified
“…Conventional holographic memory systems developers use physical multiplexing of holograms in order to achieve a high density of data record. [1][2][3][4][5][6][7] Another trend to increase the record density of data storage system is the use of advanced modulation formats, which utilize both amplitude and phase modulation to represent digital data as symbols of constellation diagram (bauds). Application of methods such as spatial quadrature amplitude modulation (SQAM) for digital data encoding onto data page and its implementation to increase the holographic memory capacity were demonstrated theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was demonstrated that computer generated Fourier holograms (CGFH) are a perspective candidate for application in holographic data storage (HDS) system design for the recording and reconstruction of binary amplitude data pages. [4][5][6][7]19) In the case of CGFH, a data page with any type of two-dimensional numeric complex function can be digitally encoded into the non-negative real valued holographic structure which can be physically realized as a diffraction optical element using amplitude-only or phase-only spatial light modulator (SLM) or transmitted onto the photosensitive carrier using a simple optical projection scheme based on amplitude-only SLMs or OLEDs. 20) Depending on the photosensitive material and post-processing methods, micro-holograms of data pages obtained in the projection schemes can be amplitude-only, phase-only or mixed amplitude and phase-modulating.…”
Section: Introductionmentioning
confidence: 99%